2022
DOI: 10.1186/s12873-022-00658-w
|View full text |Cite
|
Sign up to set email alerts
|

Independent risk factors of mortality in patients with sepsis receiving single-dose etomidate as an induction agent during rapid sequence intubation in a large tertiary emergency department in Thailand

Abstract: Background There is limited evidence regarding factors associated with mortality in septic patients receiving etomidate. This study aimed to determine independent pre-intubation factors predicting 28-day mortality in septic patients receiving single-dose etomidate as an induction agent during rapid sequence intubation (RSI). Methods This single-center retrospective cohort study included intubated septic patients receiving etomidate as an induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…Moreover, Smischney et al 8 also found that every 10-year increase in age increased the incidence of PIH by 1.33 times. Concordance with previous study, 17 higher lactate levels are not only associated with the severity of sepsis but also an increasing odds for PIH, accounting for a 2.00-times higher odds if the lactate level is >4.4 mmol/L.…”
supporting
confidence: 87%
“…Moreover, Smischney et al 8 also found that every 10-year increase in age increased the incidence of PIH by 1.33 times. Concordance with previous study, 17 higher lactate levels are not only associated with the severity of sepsis but also an increasing odds for PIH, accounting for a 2.00-times higher odds if the lactate level is >4.4 mmol/L.…”
supporting
confidence: 87%
“…While medical scientists and clinical experts agree that certain key factors can serve as prognostic indicators for sepsis, 13 different studies have identified varying high-risk factors. 14 , 15 In our study, we examined data from a cohort of 1733 septic patients and identified ten variables (MV requirement, HF requirement, NE requirement, Septicemia, MDR, thrombocytopenia, RDW-CV, CRP, AT III, and APTT) that exhibited the strongest associations with sepsis-related mortality using Lasso regression. When combined to form a predictive model, these variables yielded an AUC of 0.801.…”
Section: Discussionmentioning
confidence: 99%